Probable maximum precipitation estimation and its spatio-temporal analysis (MAUSAM, 2025)
Probable Maximum Precipitation (PMP) is the greatest depth of precipitation for a given duration meteorologically possible for a design watershed or a given storm area. It can be thought of as a reasonable upper limit of the rainfall that could be anticipated in a given region. PMP values have been estimated for 173 rainfall monitoring stations in Maharashtra, using 113 years long period daily rainfall data applying Modified Hershfield technique. Station data captures extreme behavior of rainfall in a better way as compared to gridded rainfall data sets as it represents normalized versions.  The method is based on enveloped frequency factor analysis and on the assumption that long term rainfall records well capture information on extreme rainfall events in an area. The enveloping curves were generated for each of the four meteorological sub-divisions of Maharashtra, namely Konkan & Goa, Madhya Maharashtra, Marathwada, and Vidarbha.   In Maharashtra, 1-day PMP varies from 22.57 to 95.26 cm, 2-day PMP varies from 31.66 to 127.79 cm, and 3-day PMP ranges from 36.1 to 134.22 cm. The highest values of1-3 day observed rainfall and PMP were found to be located in the Konkan and Goa sub-division stations. Most variation was observed in the Konkan and Goa sub-division stations for 1-day PMP, whereas the Madhya Maharashtra sub-division exhibitedthe highest variation for 2-day and 3-day PMP. Konkan Goa sub-division represents high rainfall and high PMP region, so more preparedness needs to be realized in this region.